Implications of Sedimentary Provenance and Regional Tectonic Evolution on the Formation Process of the South China Sea - Cui, Yuchi (Curtin University, 2024)
This study utilised a combination of petrographic, mineralogical, geochemical and isotopic analyses to investigate the Upper Mesozoic Cenozoic geological records in the northern South China Sea area. The thesis reinterprets the Mesozoic basement and explores the evolution of Mesozoic Andean-type active continental margin, highlighting the transition from active to passive margins. The research also investigated provenance and evolution of major river systems and sedimentary processes, and conducted systematic paleogeographic reconstruction. The findings provide insights into early Cenozoic magmatic activity and the South China Sea's expansion mechanism.